Disinformation and Responsibility in Young People in Spain during the COVID-19 Era - Juana Farfán; María Elena Mazo (Publications, 2021)
This paper analyzes the main variables that determine the relationship between disinformation and youth responsibility during the latest stage of the COVID-19 pandemic in Spain (from April to June 2021). Are young people keeping well informed during the COVID-19 pandemic in Spain? Are the youth behaving responsibly? This document presents several results regarding these questions. In our introduction, we establish a theoretical framework for the following concepts: disinformation, responsibility, credibility, and youth responsibility variables. Our primary interest is in communication factors. The applied methods are a reference review of the national and international literature surrounding this subject and qualitative opinion research conducted through discussion groups with young university students from private and public communication schools in Madrid. A recent study, held in June 2021, provides valuable material for this paper. The main results and findings are as follows: not being satisfied with the information received about COVID-19; knowledge about the most credible news sources; the connection between information and responsibility; and the solutions that are claimed to more responsible in this context by various youth participants. In conclusion, this paper confirms the first hypothesis of considering disinformation as a variable that causes a lack of personal responsibility among youths in complying with public health expectations. Regarding the second hypothesis, we verify that young people consider communication one of the main solutions for being more responsible. In other words, when presented with more information about COVID-19 they feel more aware of the disease.